2012
DOI: 10.1093/ajcp/138.suppl1.024
|View full text |Cite
|
Sign up to set email alerts
|

AmniSure Placental Alpha Microglobulin-1 Rapid Immunoassay for Detection of Rupture of Membranes: A Comparison Study With Clinical-Based Testing

Abstract: Iron deficiency anemia is commonly associated with thrombocytosis, although severe thrombocytopenia has been reported in rare cases. The differential diagnosis for severe thrombocytopenia (<20 k/µL) includes iatrogenic complications of medications (eg, chemotherapy, heparin), acute leukemias, immune thrombocytopenic purpura (ITP), and thrombotic thrombocytopenic purpura. A 31-year-old woman with a history of menorrhagia and 3 previous cesarean sections was admitted to the emergency department after a routine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previous studies of diagnostic tests to con rm PROM in patients with a questionable state of the membranes reported varying e cacy. The tests investigated included the fern test [7], nitrazine test [8], bronectin immunoassay [9], insulin-like growth factor binding protein-1 (IGFBP-1) test [10], alphafetoprotein (AFP) kit [11], placental α microglobulin-1 (PAMG) immunoassay [12,13], and dye injection [14]. A meta-analysis of studies that focused on the clinical use of biochemical marker tests in patients with suspected membrane rupture found that PAMG-1 and IGFBP-1 had high positive (98.4% and 87.9%, respectively) and negative (96.7% and 93.9%, respectively) predictive values, making them useful diagnostic aids [15].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of diagnostic tests to con rm PROM in patients with a questionable state of the membranes reported varying e cacy. The tests investigated included the fern test [7], nitrazine test [8], bronectin immunoassay [9], insulin-like growth factor binding protein-1 (IGFBP-1) test [10], alphafetoprotein (AFP) kit [11], placental α microglobulin-1 (PAMG) immunoassay [12,13], and dye injection [14]. A meta-analysis of studies that focused on the clinical use of biochemical marker tests in patients with suspected membrane rupture found that PAMG-1 and IGFBP-1 had high positive (98.4% and 87.9%, respectively) and negative (96.7% and 93.9%, respectively) predictive values, making them useful diagnostic aids [15].…”
Section: Discussionmentioning
confidence: 99%